Cultural superstitions and the price endings used in Chinese advertising - Simmons, Lee C. (2013)
In traditional Chinese superstition, the numerical digit 8 is associated with prosperity and good luck and the digit 4 is associated with death. An examination of the price endings used in a sample of Chinese price advertisements indicates a distinct tendency to favor the digit 8 and to avoid the digit 4. These results constitute evidence of the role of superstition in the Chinese marketplace and provide guidance for setting prices in this increasingly important market.